Analisis kesulitan siswa SMA dalam menyelesaikan soal hots menggunakan metode two-tier tes - Ahmad, Nurul Qomariyah; Noviani, Julia; Sari, Anita Permata (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2023)
High Order Thinking Skills (HOTS) are high-order thinking skills that should be owned and improved by Indonesian students to catch up with other countries, especially in the field of mathematics. This study aims to identify and describe students' difficulties in solving HOTS questions through the two-tier test method at MAN 3 Aceh Tengah. This research is a qualitative-research with document data sources on test answers, questionnaires, and interviews. The research subjects in this study were 3 subjects from class XII at MAN 3 Central Aceh. Analysis of the validity of the data used triangulation techniques, namely identifying and describing the difficulties faced by students when solving HOTS questions by analyzing the results of test answers, questionnaires and interviews. The results of the research show specifically and descriptively that students when solving analyzing indicator questions feel anxious, lack self-confidence and are unable to process information into the form of solving mathematics. In the evaluating indicator, students are not sure they can solve the questions given. So that students fail to understand the concept of solving the problems presented. Meanwhile, in the creating indicator, students still have difficulty developing their own ideas. In the indicator of creating, students are only monotonous in what the teacher teaches, without developing their creativity to solve the given problem.